Effect of low-dose rituximab treatment on autoimmune nodopathy with anti-contactin 1 antibody - Ying Hou; Chao Zhang; Xiaolin Yu; Xiaolin Yu; Wenqing Wang; Dong Zhang; Yunfei Bai; Chuanzhu Yan; Chuanzhu Yan; Chuanzhu Yan; Lin Ma; Lin Ma; et al. (Frontiers in Immunology, 2022)
BackgroundAutoimmune nodopathy with anti-contactin-1 (CNTN1) responds well to rituximab instead of traditional therapies. Although a low-dose rituximab regimen was administered to patients with other autoimmune diseases, such as myasthenia gravis and neuromyelitis optica spectrum disorders, and satisfactory outcomes were obtained, this low-dose rituximab regimen has not been trialed in anti-CNTN1-positive patients.MethodsAnti–CNTN1 nodopathy patients were enrolled in this prospective, open-label, self-controlled pilot study. A cell-based assay was used to detect anti-CNTN1 antibodies and their subclasses in both serum and cerebrospinal fluid. Clinical features were evaluated at baseline, 2 days, 14 days, and 6 months after single low-dose rituximab treatment (600 mg). The titers of the subclasses of anti-CNTN1 antibody and peripheral B cells were also evaluated at baseline, 2 days, and 6 months after the rituximab regimen.ResultsTwo patients with anti–CNTN1 antibodies were enrolled. Both patients had neurological symptoms including muscle weakness, tremor, sensory ataxia, numbness and mild nephrotic symptoms. In the field of neurological symptoms, sensory ataxia markedly improved, and the titer of anti-CNTN1 antibody as well as CD19+ B cells decreased only two days following low-dose rituximab treatment. Other neurological symptoms improved within two weeks of rituximab treatment. At the 6-month follow-up, all neurological symptoms steadily improved with steroid reduction, and both the anti-CNTN1 antibody titer and CD19+ B cells steadily decreased. No adverse events were observed after this single low-dose rituximab treatment.ConclusionsWe confirmed the clinical efficacy of low-dose rituximab by B cell depletion in autoimmune nodopathy with anti-CNTN1 antibody. This rapid and long-lasting response suggests that low-dose rituximab is a promising option for anti-CNTN1 nodopathy.